Implementation of Process-Standard Management in Science and Social Studies Learning: A Case Study of Grade V Elementary School - Nur Aviza; Rizal Rizal; Surahman Wilade; Nashrullah Nashrullah; Muhammad Nazimuddin Al Kamil; Sisriawan Lapasere (Papanda Publisher, 2026)
Process-standard management plays a crucial role in ensuring quality education, yet its implementation in integrated science and social studies (IPAS) learning under Indonesia's Merdeka Curriculum remains understudied, particularly in resource-limited elementary schools. This qualitative descriptive case study examined process-standard implementation in Grade V IPAS learning at SD Inpres Perumnas Palu through a 31-item student questionnaire (N=31), semi-structured interviews with the teacher and principal, and documentation analysis. The overall implementation achieved a mean score of 3.66/4.00 (95.6%), indicating good to very good quality. Assessment and follow-up demonstrated the strongest performance (M=3.75), while planning and implementation scored 3.65 and 3.60 respectively. Strengths included clear instructional objectives, positive classroom climate, varied teaching methods, systematic formative and summative assessment, and strong school leadership support. However, gaps emerged in student involvement in planning (M=3.13), collaborative learning opportunities (M=3.00), and critical thinking stimulation (M=3.10). An unexpected finding revealed students distinguished between structured group discussions and authentic peer collaboration. Findings confirm that while teachers successfully implement visible pedagogical practices, deeper competencies in curriculum-based planning, sustained inquiry facilitation, and comprehensive diagnostic-formative assessment require strengthened professional development and institutional support.